The Relationship of the Anti-Oxidant Bilirubin with Free Thyroxine Is Modified by Insulin Resistance in Euthyroid Subjects - Deetman, Petronella E.; Bakker, Stephan J. L.; Kwakernaak, Arjan J.; Navis, Gerjan; Dullaart, Robin P. F. (PloS one, 2014)
The strong anti-oxidative properties of bilirubin largely explain its cardioprotective effects. Insulin resistance is featured by low circulating bilirubin. Thyroid hormone affects both bilirubin generation and its biliary transport, but it is unknown whether circulating bilirubin is associated with thyroid function in euthyroid subjects. Aim is to determine relationships of bilirubin with TSH, free T4 and free T3 in euthyroid subjects without type 2 diabetes mellitus (T2DM), and to assess whether such a relationship would be modified by the degree of insulin resistance. Total bilirubin, TSH, free T4, free T3, glucose, insulin, lipids and transaminases were measured in 1854 fasting euthyroid subjects without T2DM, recruited from the general population (PREVEND cohort). Insulin resistance was assessed by homeostasis model assessment. Bilirubin was positively related to free T4 (β = 0.116, P<0.001) and free T3 (β = 0.078, P = 0.001), but bilirubin was unrelated to TSH. The relationship of bilirubin with free T4 was modified by insulin resistance with a larger effect in more insulin resistant individuals (adjusted for age and sex: β = 0.043, P = 0.056 for interaction; additionally adjusted for smoking, alcohol intake, transaminases and total cholesterol (β = 0.044, P = 0.044 for interaction). The association of bilirubin with free T4 was also modified by high density lipoprotein cholesterol (age- and sex-adjusted: β = 0.040, P = 0.072). Low bilirubin relates to low free T4 in euthyroid non-diabetic subjects. Low normal free T4 may particularly confer low bilirubin in more insulin resistant individuals.